Immune and targeted therapy for cancer: time to rethink restrictions for the treatment of the elderly and frail - Juliana Rodrigues Beal; Gustavo Schvartsman; Rodrigo Ramella Munhoz; Theodora Karnakis; Rafael Aliosha Kaliks (Brazilian Journal of Oncology)
Targeted and immunotherapy have revolutionized cancer treatment. They safely substitute for traditional chemotherapy in a significant and growing number of malignancies. In this article, we review the United States Food and Drug Administration (FDA) - approved targeted and immunotherapies, currently used in oncology and compare their safety and efficacy in young versus geriatric and frail sub-population. The results suggest an overall comparable, if not superior efficacy in several tumor types, with acceptable toxicities across the board compared to cytotoxic chemotherapy and a favorable analysis in the comparison to the results observed in the younger population. The very decision to place elderly patients on exclusive palliative care can no longer be supported based on age or frailty alone. The historical concept of medical oncologists leaning for palliative treatments for these patients needs to be revisited.